RESEARCH ON THE DYNAMICS AND TERITORIAL DISPERSION OF THE OCCUPIED POPULATION IN ROMANIA'S TOURISM IN THE PERIOD 2007-2015 - Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to analyze the evolution of the population occupied in tourism compared to the population occupied in the national economy in the period 2007-2015 using the empirical data provided by National Institute of Statistics. Index method, comparison method, descriptive statistics, Pearson correlation coefficient, linear regression function, and Herfindhal-Hirschman and Gini-Struck indices were used as methodological framework. The population occupied in tourism activities increased by 12.02 % from 155.5 thousand persons in 2007 to 174.2 thousand persons in 2015. Tourism contributes by 2.07 % to the population occupied in the economy. The Bucharest-Ilfov, Centre and SE micro-regions have the highest number of population working in tourism: 21.19%, 16.07%, and respectively 12.45%. The South West Oltenia and West micro-regions have the lowest shares of population employed in tourism. The persons working in tourism are relatively uniform distributed in the territory as confirmed by Herfindhal-Hirschman and Gini-Struck indices. The tourism structure by professional status is: 90.8 % employees, 3.8 % employers and 5.4 % self employed people, higher figures than in the national economy. Tourism absorbed more younger persons than in the national economy. About 13.5 % of the employed persons in tourism belong to the 15-24 years category and 34.5 % belong to the 25-34 years category. The correlation coefficient r=0.588 between the number of people employed in tourism and the number of units for tourists' accommodation reflects that a higher number of tourists will require a larger accommodation capacity and more employment in tourism activities. The correlation coefficient r=0.355 between the number of places (beds) and the number of persons occupied in tourism is a weak. As a final conclusion, tourism is a dynamic branch of Romania's economy with a high potential to create jobs, employ young people and also women.